2003
DOI: 10.5713/ajas.2003.555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Litter Materials on Broiler Performance and Evaluation of Manureal Value of Used Litter in Late Autumn

Abstract: A total of 168 seven days-old Arbor Acres chicks were reared in late-autumn on 4 types of litters; sawdust, rice husk, sugarcane bagasse or wheat straw up to 49 days of age to compare the growth performance, evaluate the manureal value and Coccidial oocyst population in used litter. Sadust, rice husk, sugarcane bagasse and wheat straw did not differ statistically for live weight, feed consumption, feed conversion ratio and survivability (p>0.05). However, live weight and survivability tended to increase on saw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
1
20
1
2
Order By: Relevance
“…Rice hull, a by-product of the rice industry, is one of the main litter materials used as bedding in poultry facilities worldwide (Monira et al 2003). Its primary function is to avoid direct contact of poultry with the floor, maintain the temperature balance in the facilities and absorb the moisture generated by the poultry feces.…”
Section: Introductionmentioning
confidence: 99%
“…Rice hull, a by-product of the rice industry, is one of the main litter materials used as bedding in poultry facilities worldwide (Monira et al 2003). Its primary function is to avoid direct contact of poultry with the floor, maintain the temperature balance in the facilities and absorb the moisture generated by the poultry feces.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, both litter management and disposal raise important challenges to the poultry industry, and a major parameter is its economy. Litter source material usually varies according to regions (Monira et al, 2003;Škrbić et al, 2012); sawdust, rice or oat hulls, sugarcane pulp or bagasse, chopped straw, paper mill by-products, sand, wood shavings, corn cobs, and dried leaves are often used as litter source (Swain and Sundaram, 2000). Litter is composed of the bedding material plus the excreta, feed, feathers, and water.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the lower moisture retention capacity of wood shavings and SB litters in the fifth flock produced lower temperature and relative humidity, thus increasing bird comfort and performance. Studies investigating the use of alternatives to wood shavings in bedding have reported that use of SB (Monira et al ., 2003;Araújo et al ., 2007) and other materials (Atêncio et al ., 2010;Mendes et al ., 2011) produced no differences in productive performance of birds. Survival rate of birds was also not influenced.…”
Section: Discussionmentioning
confidence: 99%